Safety Management System in Secondary Educational Institutions in Bangkok under the Office of the Basic Education Commission - Panasri, Decha; Sikkhabandit, Sowwanee; Theerawitthayalert, Panya (International Journal of Sociologies and Anthropologies Science Reviews, 2026)
Background and Aim: The 20-year National Strategy (2018-2037) and the Ministry of Education's policy emphasizes creating a safe school environment, under the concept of "Well Learning and Happiness". However, the incidents that resulted in student deaths in educational institutions over the past year have reflected inadequate safety management, and this is likely to increase. Materials and Methods: This quantitative research employed the conceptual framework of school safety scope and school safety measures. The research area covered schools under the Secondary Educational Service Area Office Bangkok 1 and 2. The sample consisted of 75 school administrators and 75 student affairs supervisors, totaling 150 participants. The sampling method used stratified sampling based on school size and simple random sampling through lottery drawing. The research instrument was a questionnaire. Data analysis was conducted using mean and standard deviation. Results: The safety management practices of secondary schools in Bangkok under the Office of the Basic Education Commission were at a high level overall (M = 4.09, SD = 0.19), with violence-related hazards receiving the highest attention (M = 4.17, SD = 0.37). The safety measures implementation demonstrated high effectiveness across all three dimensions: prevention, promotion, and protection (M = 4.28, SD = 0.25), with promotion measures showing the strongest implementation (M = 4.29, SD = 0.37). This high level indicates that schools have established comprehensive safety systems with consistent practices, though rights violation prevention requires continued attention for further improvement. Conclusion: Secondary schools in Bangkok demonstrate effective safety management with emphasis on cultivating safety awareness and preventing violence. However, there is still a need to strengthen the prevention of children and youth rights violations. These findings can be utilized as guidelines for developing national school safety standards, formulating educational safety policies, and designing training programs for school administrators and educational personnel to enhance their effectiveness.